Inventory and production management in supply chains - Silver, Edward A. (Edward Allen) 1937-; Pyke, David F.; Thomas, Douglas J. (CRC Press, Taylor & Francis Group, 2017)
Authored by a team of experts, the new edition of this bestseller presents practical techniques for managing inventory and production throughout supply chains. It covers the current context of inventory and production management, replenishment systems for managing individual inventories within a firm, managing inventory in multiple locations and firms, and production management. The book presents sophisticated concepts and solutions with an eye towards today's economy of global demand, cost-saving, and rapid cycles. It explains how to decrease working capital and how to deal with coordinating chains across boundaries.